CK2 in the spotlight: decoding its role in hematological malignancies and therapeutic applications - Zhaoyi Cai; Qiang Luo; Yuqun Zhang; Rui Meng; Ming Tian (Discover Oncology)
Abstract Protein kinase CK2 is known to have potent biological effects, and its high expression is closely associated with malignant phenotypes of tumors, especially hematological malignancies. Targeting protein kinase CK2 is a promising therapeutic direction in hematological malignancies, as it promotes the survival of tumor cells and regulates the cell cycle and enhances the resistance of tumor cells to tumor therapy. In recent years, a large number of studies have confirmed the therapeutic effect of targeting protein kinase CK2 in combination with other therapies in the treatment of hematological malignancies. Here, we reviewed the key signaling pathways regulated by protein kinase CK2, the role of protein kinase CK2 in various hematological malignant tumors, the research progress and the potential clinical application prospects.